Penerapan Metode Topsis Untuk Pemilihan Perumahan - Hari Sugiarto (Universitas Bina Sarana Informatika, 2021)
Determining which housing to choose by consumers is influenced by many factors, including price, location, facilities, environment, and house design. The housing selection process is very important so that prospective buyers do not make the wrong choice. In this study, an assessment of housing selection load was carried out based on four main factors used as a reference in decision making, namely price, location, facilities, house design, and environment. One method that can be used to solve problems in housing selection is the TOPSIS (Technique for Orders Preference by Similarity to Ideal Solution) method which is a multi-criteria decision-making method that applies the principle that the chosen alternative must have the closest distance to the ideal positive solution and the farthest distance. with a negative ideal solution. With this method consumers can make choices or make a decision by determining the weight value for each attribute, then proceed with a ranking process that will provide the best alternative from a number of alternatives, the alternative that has the highest weight value is the alternative option that has the highest priority value. Based on this method, the ranking results will be obtained which will be used as a reference in determining decision making. The result of the calculation process of the TOPSIS method is in the form of housing selection information that is closest to the choice desired by consumers who want to have an ideal home.Keywords: housing, assessment weight, topsis